Somatic Growth Features of Moderate-Late and Early Preterm Infants at Early Childhood - Selahattin Akar; Sultan Kavuncuoglu; Mustafa Ali Akın; Esin Aldemir; Ali Demirhan (Galenos Publishing House, 2021)
Objective: The aim of this study was to compare the physical growth features of preterms infants at early childhood and to evaluate the perinatal and postnatal risk factors that affect growth. Method: Somatic growth features including weight, height, and target height, of moderate-late and early preterm infants followed-up in our unit were evaluated at a mean age of 42 months. The effects of intrauterine growth characteristics (IUGC) on current growth as well as the effects of perinatal and early neonatal problems were investigated. Results: A total of 232 moderate-late preterm infants (Group I) (mean gestational age [GA]: 34.9+-1.2 weeks) and 112 early preterms (Group II) (mean GA: 29.9+-1.6 weeks) were evaluated. The ratio of retardation in height was 2.6 % and 6.3% in Group I and Group II, respectively. The rate of failure in achieving the target height was higher in Group II (3.9% vs 8%). Growth differences in terms of height and weight were not significantly different between the two groups (p>0.05). Severe intraventricular hemorrhage (IVH), hydrocephalus and invasive mechanical ventilation requirements negatively affected the growth in height and reaching the target height (p<0.05). Conclusion: The moderate-late and early preterm infants had similar growth features in terms of weight, height, and target height when evaluated at 42 months of age.